Mapeamento dos custos para tarifa de transporte no trecho Manaus – Barcelos: um estudo de caso - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The geographical scenario is huge Amazonian endowed with the largest rainforest on the planet, with rich and extensive waterways that travel great distances. It is in this immense territorial context which is inserted the logistics scenario freight and passenger transport in the State of Amazonas, with small boats called regional recreational boats or motor. Managed with informal administrative practices, not existing records of costs incurred for the pricing. This ignorance, combined with the lack of standardization of water transport of passengers makes users do not have a default value for your transfers and, also, the operator himself cannot determine if incurs in profit or loss. The work presents the mapping of the costs that make up the value of the waterway passenger transport rate in Manaus – Barcelos. The search is characterized, as their ends, as descriptive, referring to nature is applied with regard to bibliographical and documentary procedures used, the approach is qualitative and quantitative type. After analysis, it was concluded that the total costs consisting of 42% of fixed costs (salaries, social contributions, social benefits, maintenance, lubricants, pró-labore, terminals for berthing fee, depreciation) and 58% of variable costs (food and fuel). Of the total fixed cost, approximately 85% is destined to labor and social security contributions; the average variable cost is composed of: food with passengers, 25% and 75% expenditure on fuel; being the fairly high fare compared to amounts incurred to provide them and the income of the users of the system.
Keywords: Transporte aquaviário; Transporte de Passageiro; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO